Possessed by desire: A.S. Byatt's Possession and its location in postmodernism - Arthur, Susan Margaret (My University, 2009)
ABSTRACT This research report explores A. S Byatt’s ambivalent relationship to postmodernism through a critical engagement with two of her recent novels, Possession and The Biographer’s Tale. Both use the techniques, while simultaneously constituting a critique, of postmodernism. The novels challenge postmodernism, indicating Byatt’s misgivings about the continuing suitability of this mode of literary representation. Possession is examined in detail, while The Biographer’s Tale is used to provide a backdrop to the discussion of Byatt’s viewpoints. Possession is a pastiche of styles, incorporating some of Byatt’s favourite literary forms. Postmodernism allows this experimentation but disregards qualities the author values highly, such as a celebration of traditional literature and the emotional affectiveness of history. Possession considers the positive and negative aspects of the literary movement. This thesis examines Byatt’s negotiation with postmodernism and the contribution of her critical attitude towards the success of Possession.
Keywords: Possession; A.S. Byatt; post modernism